On contact modelling in isogeometric analysis - Cardoso, R. P. R.; Adetoro, O. B. (European Journal of Computational Mechanics, 2017)
IsoGeometric Analysis (IGA) has proved to be a reliable numerical tool for the simulation of structural behaviour and fluid mechanics. The main reasons for this popularity are essentially due to: (i) the possibility of using higher order polynomials for the basis functions; (ii) the high convergence rates possible to achieve; (iii) the possibility to operate directly on CAD geometry without the need to resort to a mesh of elements. The major drawback of IGA is the non-interpolatory characteristic of the basis functions, which adds a difficulty in handling essential boundary conditions and makes it particularly challenging for contact analysis. In this work, the IGA is expanded to include frictionless contact procedures for sheet metal forming analyses. Non-Uniform Rational B-Splines (NURBS) are going to be used for the modelling of rigid tools as well as for the modelling of the deformable blank sheet. The contactmethods developed are based on a two-step contact search scheme, where during the first step a global search algorithm is used for the allocation of contact knots into potential contact faces and a second (local) contact search scheme where point inversion techniques are used for the calculation of the contact penetration gap. For completeness, elastoplastic procedures are also included for a proper description of the entire IGA of sheet metal forming processes.